In-situ investigation of strain partitioning and microstructural strain path development up to and beyond necking. (15th August 2021) - Oh, Hyun Seok; Biggs, Krista; Güvenç, Onur; Ghassemi-Armaki, Hassan; Pottore, Narayan; Tasan, C. Cem
Graphical abstract: Image, graphical abstract Abstract: Multi-phase metallic materials exhibit significant levels of strain partitioning and localization when plastically deformed. Connecting these microstructural processes to macroscopic limits of uniform deformation, e.g., plastic instability and fracture, can reveal guidelines for damage-resistant microstructure design. This connection, however, is hindered due to the absence of strain partitioning and localization data from high strain levels, near and beyond necking. A parallel gap in our current understanding of the plasticity of multi-phase materials is regarding the spatial variations in strain path development at the micro-scale. Microscopic digital image correlation, the most powerful experimental method to provide such insights, is typically limited to low strain levels (< ~15%) due to crystal-plasticity- or damage-induced surface topography evolution. Here, we address these challenges by developing a practical method that relies on serial in-situ scanning electron microscope (SEM) mechanical tests of samples pre-strained to different levels. Applying this method to a dual-phase steel, we observe that ferrite and martensite on average exhibit a linear strain partitioning trend throughout the deformation. However, the highly-deformed ferrite regions (i.e., the top 4% most strained ferritic subsets) exhibit an exponential increase in the level of strain they accommodate, as well as sequential activation of the strain localization processes in different microscopic strain paths. Martensitic constituents play an important role in the strain localization processes and the resulting microscopic strain paths.